Acessibilidade - O papel das tecnologias assistivas e educacionais no processo de aquisição de conhecimento de alunos surdos - Andrade, Andreia Almeida dos Santos de (Universidade Federal do Tocantins, 2024)
This research performs a bibliographical review on Digital Information and Communication Technologies (TDIC) and Assistive and Educational Technologies that can be applied in teaching deaf students. It aims to identify which digital, assistive and educational technologies are effective in the process of acquiring knowledge for deaf students. The methodology for the development of this research was the qualitative approach, of an applied nature. As for the objectives, it was exploratory with bibliographic procedures. During the work, some digital, assistive and educational technologies were identified in which digital resources are used that support the development and learning of deaf students, contributing to a better acquisition of knowledge, valuing their specificities and the deaf culture.